Management Science Foundations and Innovations - Machado, Carolina; Davim, J. Paulo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents the skills required in business and management careers. The management tools provided within this text can be very useful for beginners in the study of management area, as well as to those pursuing a managerial career in different types of organization. It serves as a refreshment in the management sciences foundations. Subjects such as accounting, marketing, human resources, operations, finance are treated in detail, giving the reader the background that can be applied to a variety of real world business situations. The book also covers the latest developments in management research activity, promoting discussion and the exchange of information on principles, strategies, models, techniques, methodologies and applications in the management and business area.
Management -- Organizational behaviour -- Corporate social responsibility -- Human resource management -- Financial management -- Marketing management -- Operations management -- Information management -- International management -- Accounting -- International business -- Business management -- Business law -- Statistics -- Economics -- Culture and organizational behaviour -- Competitive management practice.
Keywords: Industrial engineering; Production engineering; Management; Industrial organization; Education, Higher; Industrial and Production Engineering; Management; Organization; Higher Education